Mechanical Behaviour and Thermal Properties of Pine Apple Leaf Fiber Reinforced Vinyl Ester Composites. (19th April 2022) - Refaai, Mohamad Reda A.; Tamilarasan, U.; Kumar, K. Dilip; Karthe, M.; Anbu, C.; Yishak, Simon
Abstract : Despite its mechanical and environmental properties, pineapple leaf fibers (PALF) are used as a home threading material in India. In addition, the effects of abrasive combing and pretreatment techniques on fiber and composite characteristics were examined in this work. Using PALF vascular bundles separated from different regions of the leaves did not affect the mechanical aspects of pineapple leaf fiber-vinyl ester composites. PALF fibers performed equally in strengthening composite flexural properties under static loading, regardless of diameter or location, with a much lower weight percentage and combined pressure. Tests at higher speeds revealed that the PALF-vinyl ester composite was more robust with more delicate bundles. Reinforcing composites that do not require a high degree of hardness can benefit from the cleaner, more delicate bundles produced by abrasive combing.